Behavior of the bottomside electron density profile over Pruhonice - Mosert, Marta Estela (2004)
Ionosonde data obtained at Pruhonice (50.0°N; 15.0°E) during different times of the day, seasons and periods of the solar cycle are used to study the behavior of the F2 thickness and shape parameters, B 0 and B 1 , respectively. Experimental values of both parameters are compared with the predictions of the latest version of the International Ionosphere Reference, IRI-2000. A preliminary analysis of the variability of the ionospheric parameters f o F2, M(3000)F2, f o F1 and f o E is also done using the variability index Cup-Clo = interquartile range/median. The study shows that: (i) the IRI Gulyaeva B 0 option reproduces better the experimental electron density profiles than the B 0 -Table option, (ii) the new values introduced for BI in the IRI-2000 model are more realistic than the constant value of three adopted by the IRI-90 and IRI-95 versions, (iii) the variability in the E and F1 regions is less than that observed in the F2 region, (iv) the M(3000)F2 factor exhibits low variability. Additional studies will be done in order to contribute to the development of a model for the variability indices used in this study.